The Effect of Seed Weight on Growth of Seaweeds Kappaphycus alvarezii in Integrated Marine Aquaculture of Ekas Bay, East Lombok Regency - Lalu Sofyan Satria Jaya; Muhammad Junaidi; Nanda Diniarti (Jurnal Biologi Tropis, 2022)
Integrated marine aquaculture or known as Integrated Multi-Tropical Aquaculture (IMTA) is an alternative development in aquaculture activities under the concept of environmental conservation. There are several important aspects in supporting the success of seaweed cultivation including the use of the right weight of seeds at the beginning of cultivation activities. The purpose of this study was to analyze the effect of seedling weight on the growth of Kappaphycus Alvarezii seaweed cultivated in integrated cultivation areas and to determine the best use of seed weight. This study used a completely randomized design (CRD) consisting of 4 treatments and 3 replications to obtain 12 experimental units. The treatments used were the initial seedling weights of 50 g, 100 g, 150 g, and 200 g. The results showed that the effect of different seed weights on the integrated cultivation system with the longline method showed that the absolute average growth obtained ranged from 57.67 g to - 149.00 g while the average specific growth rate of seaweed ranged from 1.28%/day to - 3 ,31%/day and the best chlorophyll-a was found in the 50 g treatment with a value range of 0.628 mg/L to - 1.520 mg/L. It can be concluded that the use of seed weight gave a significantly different effect on the absolute growth and specific growth rate of Kappaphycus Alvarezii seaweed that was cultivated in an integrated manner and the use of the best seed weight with the best weight was 50 g.